2023
DOI: 10.3390/vaccines11040721
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of University Students towards Mandatory COVID-19 Vaccination Policies: A Cross-Sectional Survey in Rome, Italy

Abstract: Mandatory vaccination (MV) against COVID-19 is a contentious topic. In this study, we used logistic regression models to identify attitudes among Sapienza University students towards MV for COVID-19. We considered three different scenarios: mandatory COVID-19 vaccination (MCV) for healthcare workers (HCWs) (Model 1), for all people aged ≥ 12 years (Model 2), and for admission to schools and universities (Model 3). We collected 5287 questionnaires over a six-month period and divided these into three groups (Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Despite this value being slightly lower than the 85% officially reported by the National Institute of Health in the same period for the general Italian population in the age range 40–59 years [ 22 , 23 ], an age category comparable with that of our sample, it was higher than that found in Australia [ 24 ] and Mexico [ 25 ] among people who injected drugs (41% and 39%, respectively). Hence, these data suggest that the vaccination policies adopted by the Italian government, such as the implementation of mandatory vaccinations for specific subgroups of workers or people aged 50 or above, together with the introduction of a green pass for everyone who wanted to enter public locations, may have contributed to the relatively high degree of vaccine uptake in the SUD subgroup, directly or indirectly [ 26 ]. It is worth mentioning the different times at which the surveys were conducted, with our study enrolling participants one year after the COVID-19 vaccine became available, i.e., from two to four months after the Australian and Mexican investigations; however, it is unlikely that the discrepancy between studies is attributable to this factor alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this value being slightly lower than the 85% officially reported by the National Institute of Health in the same period for the general Italian population in the age range 40–59 years [ 22 , 23 ], an age category comparable with that of our sample, it was higher than that found in Australia [ 24 ] and Mexico [ 25 ] among people who injected drugs (41% and 39%, respectively). Hence, these data suggest that the vaccination policies adopted by the Italian government, such as the implementation of mandatory vaccinations for specific subgroups of workers or people aged 50 or above, together with the introduction of a green pass for everyone who wanted to enter public locations, may have contributed to the relatively high degree of vaccine uptake in the SUD subgroup, directly or indirectly [ 26 ]. It is worth mentioning the different times at which the surveys were conducted, with our study enrolling participants one year after the COVID-19 vaccine became available, i.e., from two to four months after the Australian and Mexican investigations; however, it is unlikely that the discrepancy between studies is attributable to this factor alone.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived risk of contracting COVID-19 is among the most important factors that influence both attitudes and behavior [ 26 , 35 ]. In our study, participants showed greater concern that their loved ones or other people might become infected than that they themselves would contract the virus, suggesting that participants did not feel at particularly high risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we are interested in how information framing affects willingness and perceptions toward COVID-19 vaccination among university students in Italy. Previous studies have addressed vaccination intentions and attitudes among university students in Italy [ 20 , 21 ] and in other European countries (e.g., Germany [ 22 ]; see also [ 23 ] for a review).…”
Section: Introductionmentioning
confidence: 99%